Long-Term Effects of Altered Photoperiod During Pregnancy on Liver Gene Expression of the Progeny - Carmona, Pamela; Pérez, Bárbara; Trujillo, Carlos; Espinosa, Gabriel; Miranda, Fernando; Mendez, Natalia; Torres-Farfan, Claudia; Richter, Hans G.; Vergara, Karina; Brebi, Priscilla; Sarmiento, José (Frontiers in Physiology, 2019)
Experimental and epidemiological studies have revealed a relationship between an adverse intrauterine environment and chronic non-communicable disease (NCD) like cardiovascular disease (CVD) in adulthood. An important risk factor for CVD is the deregulation of the fibrinolytic system particularly high levels of expression of plasminogen activator inhibitor 1 (Pai-1). Chronic exposure to altered photoperiod disrupts the circadian organization of physiology in the pregnant female, known as gestational chronodisruption, and cause long-term effects on the adult offspring’s circadian physiology. The Pai-1 expression is regulated by the molecular components of the circadian system, termed clock genes. The present study aimed to evaluate the long-term effects of chronic photoperiod shifts (CPS) during pregnancy on the expression of the clock genes and the fibrinolytic system in the liver of adult male offspring. Our results using an animal model demonstrated statistically significant differences at the transcriptional level in males gestated under CPS. At 90 days of postnatal age, the liver transcript levels of the clock gene Bmal1 were downregulated, whereas Rorα, Rorγ, Nfil3, and Pai-1 were upregulated. Our data indicate that CPS during pregnancy affects gene expression in the liver of male adult progeny, showing that alteration of the photoperiod in the mother’s environment leads to persistent effects in the offspring. In conclusion, these results reveal for the first time the long-term effects of gestational chronodisruption on the transcriptional activity of one well-established risk factor associated with CVD in the adult male offspring.